Long-term bowel dysfunction following low anterior resection - Dulskas, Audrius (Sci Rep, 2020)
Study aimed to assess long-term bowel function in patients who underwent low anterior resection for cancer five and more years ago. Patients who underwent low anterior resection for rectal cancer from 2010 to 2015 at National Cancer Institute were prospectively included in our study. They were interviewed using low anterior resection syndrome (LARS) score and Wexner questionnaire. We also assessed possible risk factors of postoperative bowel disorder. 150 patients were included in our study. Of them 125 (83.3%) were analysed. The median age at diagnosis was 62 years (40–79), and the average time of follow-up was 7.5 years (5–11). Overall, 58 (46.4%) patients had LARS, of them 33 (26.4%)—major LARS and 25 (20%)—minor LARS and 67 (53.6%) reported no LARS. Wexner score results were: normal in 43 (34.4%) patients, minor faecal incontinence—55 (44%), average faecal incontinence—18 (14.4%), complete faecal incontinence—9 (7.2%). 51 patients (40.8%) had tumour in the upper third rectum, 51 (40.8%)—in the middle and 23 (18.4%)—lower third. Preoperative (chemo)radiotherapy was the only significant risk factors for developing LARS in univariate analysis. Our study showed that only preoperative radiotherapy may be associated with more late problems in defecation after rectal cancer surgery. Trial registration: NCT03920202.